BUYERS 'PERCEPTION OF THE IMPACT OF THE LATEST REGULATION ON IMPORTED GOODS TAX VI E-COMMERCE - Ahmad, Hamzah; Saputri, Sri Ayu; Muslim, Muslim; Lannai, Darwis; Shaleh, Musliha (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
This study aims at how buyers' perceptions of the latest regulations applied by the government regarding taxes on imported goods via e-commerce. The data in this study were obtained by conducting a question and answer system directly to the parties involved in the interview process regarding the latest regulations on the import tax on goods for Buyers to obtain the necessary information, which is carried out at the Karebosi Link shopping center.This study uses primary and secondary data by conducting direct research in the field by thoroughly describing the data obtained during the research process, with a sample of 10 people who like to shop for productsimported. The method of data analysis using descriptive qualitative is to thoroughly describe the data obtained during the research process, namely the reduction, presentation of data and drawing conclusions. The results of this study found that most of the Buyers who agreed with the latest Regulation of the Ministry of Finance Customs and Excise regarding Imposition of Imported Goods Tax for those who carry out transactions of imported goods products online or via e-commerce for several reasons, namely because with this regulation there will be many new impacts both for the government, UMKM and Community